2001
DOI: 10.1289/ehp.01109471
|View full text |Cite
|
Sign up to set email alerts
|

A rat mammary tumor model induced by the organophosphorous pesticides parathion and malathion, possibly through acetylcholinesterase inhibition.

Abstract: Environmental chemicals may be involved in the etiology of breast cancers. Many studies have addressed the association between cancer in humans and agricultural pesticide exposure. Organophosphorous pesticides have been used extensively to control mosquito plagues. Parathion and malathion are organophosphorous pesticides extensively used to control a wide range of sucking and chewing pests of field crops, fruits, and vegetables. They have many structural similarities with naturally occurring compounds, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 23 publications
3
86
1
4
Order By: Relevance
“…The Agency subsequently considered the SAP recommendations and concluded that the cancer classification should remain as "suggestive." Additionally, the CARC recently evaluated a publication by Cabello et al (2001) and concluded that the paper provided insufficient basis for revising the cancer classification for malathion. Furthermore, the chronic dietary risk assessment is considered protective of any potential carcinogenic effects.…”
Section: F Carcinogenicitymentioning
confidence: 99%
“…The Agency subsequently considered the SAP recommendations and concluded that the cancer classification should remain as "suggestive." Additionally, the CARC recently evaluated a publication by Cabello et al (2001) and concluded that the paper provided insufficient basis for revising the cancer classification for malathion. Furthermore, the chronic dietary risk assessment is considered protective of any potential carcinogenic effects.…”
Section: F Carcinogenicitymentioning
confidence: 99%
“…Parathion (O,O-diethyl O-(4-nitrophenyl) phosphorothioate) and malathion (diethyl 2-[(dimethoxyphosphorothioyl)sulfanyl]butanedioate) that are extensively used to control a wide range of sucking and chewing pests of field crops, fruits and vegetables have many structural similarities with naturally occurring compounds, and their primary target of action in insects is the nervous system; they inhibit the release of the enzyme acetylcholinesterase at the synaptic junction [15,96]. In rats parathion and malathion were found to induce changes in the epithelium of mammary gland influencing the process of carcinogenesis and such alterations occurred at the level of nervous system by increasing the cholinergic stimulation.…”
Section: Organophosphorous Pesticidesmentioning
confidence: 99%
“…In rats parathion and malathion were found to induce changes in the epithelium of mammary gland influencing the process of carcinogenesis and such alterations occurred at the level of nervous system by increasing the cholinergic stimulation. Mammary tumour incidence in the parathion-treated rats was 14.3% and in malathion-treated animals was 24.3%, and treating the animals with atropine (which acts to oppose the cholinergic effects of the organophosphates) allowed the milk ducts to develop more normally and prevented the mammary cancers [15]. Parathion and malathion induced malignant transformation of breast cells through genomic instability altering p53 and c-Ha-ras genes considered pivotal to cancer process [97].…”
Section: Organophosphorous Pesticidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many carcinogens are genotoxic and initiate cancer development by causing DNA damage and mutation, while non-genotoxic carcinogens mostly induce neoplastic cell transformation and promote cell proliferation by different mechanisms, such as avoiding apoptosis, stimulation of growth factors, and avoiding growth suppression signals. Experimental in vitro and in vivo studies have shown that several OPs exert genotoxic activity (Bolognesi, 2003), and there are also reports showing that OPs can induce neoplastic transformation of cells (Cabello et al, 2001;Isoda et al, 2005). OPs have been reported • to be weakly mutagenic in bacteria, but mutagenic in yeast (IARC, 1987); • to induce DNA damage in peripheral lymphocytes in vitro (Blasiak and Kowalik, 1999;Ündeger and Basaran, 2005) and in vivo in occupationally exposed workers (GarajVrhovac et al, 2000); • to induce chromosomal aberrations and sister chromatid exchange (Galloway et al, 1987);…”
Section: Genotoxicity and Carcinogenicity Of Opsmentioning
confidence: 99%